Evaluasi Unjuk Kerja Screw Compressor UP5-15-10 di PT XYZ - Muhammad Rifqi Abiyyi; Hernawan Novianto (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
This paper aims to evaluate the efficiency of screw compressor UP5- 15-10 used at PT XYZ. Screw compressor efficiency is a key factor in the operation of gas processing facilities, then a good understanding of screw compressor operation can improve operational efficiency and reduce energy consumption. The compressor used in this KKW is an Ingersoll Rand UP5-15-10. The UP5-15-10 compressor is used to power pneumatic tools and instrumentation equipment. The UP5-15-10 compressor is included in the rotary type positive displacement compressor, the compressor uses ambient air as its working fluid. UP5-15-10 screw compressor operation, including design data from the manual book and actual data such as incoming air capacity of 65 CFM at a temperature of 186 F with a pressure of 135 Psia getting a power of 13.74 kW from the power specification data of 15 kW obtained efficiency of 91%. The decrease in power in screw compressor UP5-15-10 by 9% is due to the difference in intake capacity between design and actual conditions, this is caused by process needs.